HLA-DQ2/DQ8 frequency in adult patients with celiac disease, their first-degree relatives, and normal population in Turkey - Şafak Meriç Özgenel; Tuncer Temel; Hava Üsküdar Teke; Pınar Yıldız; Hüseyin Korkmaz; Ayşegül Özakyol (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Celiac disease is an autoimmune, familial disease that results in susceptibility to gluten in cereal and cereal products in genetically susceptible individuals. The aim of the present study was to investigate the presence of HLA-DQ2/DQ8 in patients with celiac disease, their first-degree relatives, and healthy community. Materials and Methods: HLA-DQ2/DQ8 analysis was performed in adult patients with celiac disease ≥18 years old (94 patients), their first-degree relatives (89 people), and healthy group (102 individuals). Anemia, osteoporosis, and diarrhea were interrogated in the celiac patient group and also anti-tissue transglutaminase, anti-endomysium, and anti-gliadin antibodies were recorded. Results: There was a significant relationship between HLA-DQ2/DQ8 presence in all groups, and the distribution of HLA-DQ2/DQ8 in all groups was different (p=0.000). No statistically significant correlation was found between the HLA tissue groups and diarrhea (p=0.087), osteoporosis (p=0.215), anemia (p=1.000), tissue transglutaminase antibodies (p=0.295), anti-gliadin antibodies (p=0.104), and anti-endomysium antibodies (p=0.243) in the celiac patient group. Conclusion: HLA-DQ2/DQ8 can be used to diagnose celiac disease particularly when the tests are useless and to screen first-degree relatives. Cite this article as: Özgenel ŞM, Temel T, Üsküdar Teke H, Yıldız P, Korkmaz H, Özakyol A. HLA-DQ2/DQ8 frequency in adult patients with celiac disease, their first-degree relatives, and normal population in Turkey. Turk J Gastroenterol 2019; 30(4): 321-5.